Barley research in India: Retrospect & prospects - Kumar, Vishnu Kumar; Khippal, Anil Khippal; Singh, Jogendra Singh; R, Selvakumar; Malik, Rekha; Kumar, Dinesh; Kharub, Ajit Singh; Verma, Ramesh Pal Singh; Sharma, Indu (Journal of Cereal Research, 2014)
Barley is one of the founder crops of old world agriculture and was one of the first domesticated cereals. It is fourth largest cereal crop after maize, wheat and rice in the world with a share of 7 per cent of the global cereal production. The crop is considered as poor manâ€™s crop and better adaptable to problematic soils and marginal lands. It is not only useful for malting, feed and food purposes but also its Î²-glucans is helpful in lowering the risk of cardio-vascular diseases. Prior to the inception of AICRP on Barley, pure line selections in the indigenous land races were employed, which resulted in the development of several barley varieties like NP 13, NP 21 (New Pusa), C 251, K 12, K 18, K 24 (Kanpur, UP), BR 22 & BR 32 (Sabour, Bihar), T4, T5, C 138 and C 164 (United Punjab). The All India Coordinated Barley Improvement Project (AICBIP), involving ICAR and SAU centers was initiated in 1966-67 to do the collaborative research. During the IXth five year plan, both barley and wheat coordinated projects were merged and combined programme was named as â€œAll India Coordinated Wheat and Barley Improvement Projectâ€ in 1997 and this arrangement is being continued since then. Keeping in mind the priorities as abiotic, biotic stress, dual, malt and food purposes, a total of 122 barley varieties and 15 genetic stocks, agrotechnologies and disease and pest management strategies have been developed from the barley improvement programme and are described in this review article.